The Efforts to Control and Prevent Cervical Cancer Through Early Detection Using The VIA Test in Health Office of East Java Province - Zulham, Riza Muhammad; Wahyuni, Chatarina Umbul; Isfandiari, Muhammad Atoillah; Huda, Hasan (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-